الافلام الكرتونية و تطوير مهارات اللغة لدى الطفل ماشا و الدب "دراسة حالة - . دفاف سميرة; .عبد الرزاق غزال (جامعة محمد بوضياف -المسيلة, 2024)
تهدف هذه الدراسة إلى استكشاف تأثير الأفلام الكرتونية على تطوير مهارات اللغة لدى الأطفال، مع التركيز على مسلسل "ماشا والدب" كدراسة حالة. تعتبر الأفلام الكرتونية وسيلة ترفيهية وتعليمية يمكن أن تلعب دوراً مهماً في تعزيز القدرات اللغوية عند الأطفال، حيث يتعرضون لمواقف مختلفة تتطلب تفاعلاً لغوياً وتساهم في توسيع مفرداتهم وتحسين مهارات الاستماع والفهم. في هذا السياق، تم تحليل "ماشا والدب" كنموذج يجمع بين الترفيه والتعليم، مع دراسة كيفية تأثير شخصيات المسلسل والأحداث والمواقف المختلفة على تطور اللغة لدى الأطفال الذين يشاهدونه. Summary: This study aims to explore the impact of cartoons on the development of children's language skills, focusing on the animated series Masha and the Bear as a case study. Cartoons are both entertaining and educational, and they can play a significant role in enhancing children's language abilities. By exposing children to different situations that require linguistic interaction, cartoons help expand their vocabulary and improve their listening and comprehension skills. In this context, Masha and the Bear was analyzed as a model that combines entertainment and education, examining how the characters, events, and different scenarios in the series contribute to the language development of children who watch it.